(untitled) (Journal of Computational Mathematics, 1992)
In this paper, the dimensions of spaces S^μ_k(Δ_n)(k≥ 2^nμ +1) are obtained, where (Δ_n) is a general simplicial partition of a bounded region with piecewise linear boundary. It is also pointed that the singularity of spaces S^μ_k(Δ_n) can not disappear when n≥ 3 no matter how large k is. At the same time, a necessary and sufficient condition that Morgen and Scott's structure is singular is obtained.